A Note on Some New Generalized Wavelets. (4th July 2022) - Zothansanga, A.; Khanna, Nikhil; Kaushik, S. K.; Kumar, Dilip
Abstract : In this paper, we define new real wavelets based on the Hartley kernel and Boas transforms. These wavelets have possible application in analyzing both the symmetries of an asymmetric real signal. We give various results to obtain their higher vanishing moments. Finally, we give a sufficient condition under which Hartley-Boas-Like wavelets associated with Riesz projector forms a convolution filter with transfer function vanishing for the positive frequencies.